Valuing Biodiversity from an Economic Perspective: A Unified Economic, Ecological, and Genetic Approach - Brock, William A; Xepapadeas, Anastasios (American Economic Review, 2003)
We develop a conceptual framework for valuing biodiversity from an economic perspective. We argue for a dynamic economic welfare measure of biodiversity that complements the literature on benefit-cost approaches and genetic distance/phylogenic tree approaches. Using a unified model of optimal economic management of an ecosystem under ecological and genetic constraints, we identify gains from management policies leading to a more diverse system, using the Bellman state valuation function of the problem. We show that a more diverse system could attain a higher value although the genetic distance of the species in the more diverse system could be almost zero.